Critical state analysis of instability of shield tunnel segment lining. (February 2020) - Wang, Shimin; Wang, Xianming; Chen, Bing; Fu, Yanbin; Jian, Yunqi; Lu, Xixi
Abstract: The prevention and treatment of disease in an underwater shield tunnel segmental lining structure is a recognized issue. It is obvious that the mechanism of damage and instability of the segmental lining structure has a strong guiding significance for the scientific management of diseases. In this paper, the study on the progressive instability and failure process of the large-diameter underwater shield tunnel segmental lining structure from microscopic damage of the material to overall instability of the structure is carried out by model test method. The progressive failure process is divided into three stages: initial elastic phase, local damage phase and overall instability failure phase. The concept of the critical instability state of the segmental lining structure is put up and the method how to determine the correct critical instability point is given. And the influences of the assembly method, the position of the capping block, the lateral pressure coefficient of the stratum and the amount of water pressure on the deformation characteristics and the critical instability state of the segmental lining structure are respectively analyzed. The results show that (1) compared with the structure with seam-assembled segments, the structure with staggered assembled segments has a larger instability start load, and its displacement convergence value and ellipticity are smaller. The structure with staggered assembly segments has a higher bearing capacity; (2) for the structure with staggered assembled segment, the ultimate bearing capacity of the capping block at vault is smaller than that of the capping block at left haunch, and it is not advisable to place the capping block at vault; (3) the high water pressure and high lateral pressure coefficient within a certain range can improve the bearing capacity of the segmental lining structure.